Respons jagung manis sebagai tanaman sela kelapa sawit belum menghasilkan terhadap pupuk kandang ayam - Bukri, Bukri; Mariyani, Anis Tatik; Nusifera, Sosiawan; Riduan, Ahmad; Irianto, Irianto (Jurusan Agroteknologi, 2024)
Sweet corn is a horticultural commodity that considerably has the development potential between immature oil palms (2 years). The experiment aimed to determine the response of sweet corn’s variety as an intercrop in immature oil palms to various doses of chicken manure. The research was conducted in Muhajirin Village, Muaro Jambi Regency in February-April 2023. The experiment was arranged in a factorial pattern group randomized design repeated three times. The first factor was sweet corn varieties consisting of